Strategic Relationship Maintenance Gaps Between Macro-Investors and Local Communities in Nusantara Capital City - Dananjaya, Ahmad Ghazy (Journal of Regional and Rural Studies, 2026)
The development of the Nusantara Capital City (IKN) requires cohesive stakeholder collaboration to ensure long-term regional stability. However, early observations indicate disparities in how the central authority maintains relationships with different actors. This study aims to evaluate the effectiveness of strategic relationship maintenance between the IKN Authority and macro-investors compared to local communities and micro, small, and medium enterprises (MSMEs). Utilizing an interpretivist-constructivist single-case study design, the research was conducted in East Kalimantan and Jakarta from March to November 2025. Data were gathered through in-depth interviews with 122 informants representing the Hexa-Helix elements, alongside netnography and NVivo-assisted thematic and sentiment analysis. The findings reveal a distinct service gap: macro-investors receive preferential facilitation through direct coordination channels and fiscal incentives, while local micro-economic actors face rigid bureaucratic procedures with minimal socio-economic capacity-building support. Sentiment analysis confirms this divergence, showing high optimism among government and business actors but substantial negative sentiment among local communities and academics. The study concludes that an "Institutional Empathy Deficit" exists, undermining procedural justice and public trust. The paper recommends establishing a dedicated MSME Assistance Helpdesk and integrating a Creating Shared Value (CSV) model to foster an inclusive, collaborative governance structure that prioritizes both macro-economic growth and local socio-economic resilience.